Optimization of The Utilization Of The Road Health Services in The General Hospital of Kertha Usada, Singaraja, 2019 - I Gede Budayana (Journal for Quality in Public Health, 2020)
The research design used was a quantitative study using an observational approach with a cross sectional study design that is data collection that would be measured only once and without any treatment to 272 respondents. Data analysis techniques using descriptive analysis and linear logistic regression test. The results showed that the community characteristics of the 272 respondents studied, based on predisposing factors, amounted to 54.8% aged 26-45 years, 57% female sex with the most undergraduate education by 32% and the most work did not work 27%. As many as 77.9% of respondents felt confident. Based on the enabling factors, most respondents (69%) earn> Rp. 1,800.00 - and all have health insurance (BPJS), with the largest distance> 5 km of 58.1% and the most frequent family treatment habits to the hospital that is 46.7%. Based on the factor of need for illness, the majority of respondents 61% had complaints of pain in the low category and the severity of pain in the severe category of 51.5%. The level, patient satisfaction at the Kertha Usada Hospital based on the results of the study amounted to 68.4% with a good category. The results of linear regression analysis between community characteristics and patient satisfaction with the utilization of health services stated that the variables of age, sex and patient satisfaction have an influence on the utilization of health services. Whereas based on the results of statistical analysis using a linear logistic regression test showed that the value of the Omnibus Test was 75,246 on (Chi-square) with a significance of 0,0005 (<0.05) so that it refused H0 and accepted H1, which showed that it could have a real influence on the model which is used, or in other words the model is declared FIT. Optimizing the utilization of health services affects the service system, the factors that affect service and patient satisfaction in hospitals